Adhesions and endometriosis: challenges in subfertility management$d(an expert opinion of the ANGEL-The ANti-Adhesions in Gynaecology Expert PaneL-group) - Wilde, Rudy Leon de; Wallwiener, Markus; Alvarez, J.; Brölmann, H.; Campo, R.; Cheong, Y.; Lundorff, P.; Pawelczyk, L.; Roman, H.; Spiezio Sardo, A. di (Archives of gynecology and obstetrics, 2016)
There is molecular evidence that endometriosis has a negative impact on the ovaries, although the exact pathophysiology concerning endometriosis-associated subfertility is not known. The negative impact on the tubo-ovarian unit can be directly by distorting the anatomy, indirectly by invoking inflammation or by oxidative damage with poorer-quality oocytes. Endometriosis even seems to have a negative effect on pregnancy outcome after in vitro fertilization.
Gesehen am 14.12.2018